Child audiences in South Africa - Daan van Vuuren (Communicare)
The consumption of media – especially radio and television – by children has been a topic of research for decades now. Although extensive research has been published on the effects of the media, also in South Africa, very few (if any) publications address the issue of when and what children are viewing in South Africa, and if something should be done about this behaviour. In this article, specific examples of the viewing patterns of children between the ages of 7 and 15 are presented in the context of unacceptable material to which they are exposed. The different roles of parents, broadcasters and legislators are discussed, against the backdrop of recent literature, in an attempt to suggest a way forward.